2018
DOI: 10.1016/j.celrep.2018.01.074
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Ablation of miR-33 Increases Food Intake, Enhances Adipose Tissue Expansion, and Promotes Obesity and Insulin Resistance

Abstract: SUMMARYWhile therapeutic modulation of miRNAs provides a promising approach for numerous diseases, the promiscuous nature of miRNAs raises concern over detrimental off-target effects. miR-33 has emerged as a likely target for treatment of cardiovascular diseases. However, the deleterious effects of long-term anti-miR-33 therapies and predisposition of miR-33−/− mice to obesity and metabolic dysfunction exemplify the possible pitfalls of miRNA-based therapies. Our work provides an in-depth characterization of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
98
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 54 publications
4
98
0
Order By: Relevance
“…Therefore, miR-33a and SREBP2 act synergistically to efficiently increase cellular cholesterol levels by inhibiting cellular cholesterol efflux and increasing lipid uptake and intracellular synthesis, respectively. While previous studies suggested that miR-33 may represent therapeutic target for the treatment of cardiovascular disease [24,25], a recent work showed that miR-33 deletion in mice results in dyslipidemia, obesity, and insulin resistance [26], assigning a role for miR-33 that is much more complex than what has been considered so far. Such complexity has also been illustrated in humans by the fact that miR-33 levels are surprisingly elevated in pediatric patients affected by familial hypercholesterolemia (FH) [27].…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, miR-33a and SREBP2 act synergistically to efficiently increase cellular cholesterol levels by inhibiting cellular cholesterol efflux and increasing lipid uptake and intracellular synthesis, respectively. While previous studies suggested that miR-33 may represent therapeutic target for the treatment of cardiovascular disease [24,25], a recent work showed that miR-33 deletion in mice results in dyslipidemia, obesity, and insulin resistance [26], assigning a role for miR-33 that is much more complex than what has been considered so far. Such complexity has also been illustrated in humans by the fact that miR-33 levels are surprisingly elevated in pediatric patients affected by familial hypercholesterolemia (FH) [27].…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, some microRNAs have been implicated in dietinduced obesity. Data from Price et al showed that miR-33 null mice had increased food intake, enhanced adipose tissue expansion, and a predisposition to develop diet-induced obesity and insulin resistance (17). miR-143 was found to be upregulated in mesenteric fat of high-fat diet-induced mice (18).…”
Section: Introductionmentioning
confidence: 99%
“…Our group and others initially identi ed microRNA-33 (miR-33) as crucial regulator of cellular lipid homeostasis and lipoprotein metabolism, controlling downstream target genes including ABCA1 and ABCG1 10,11,12,13,14,15,16 . The bene ts of miR-33 de ciency on atherosclerosis development are attributed to its protective effects in macrophages 12 Therapeutic inhibition of miR-33 in the mice and non-human primates raises plasma high density lipoprotein (HDL) levels and inhibits the progression of atherosclerosis by increasing HDL levels/functionality or enhancing cholesterol e ux through induction of ABCA1 and ABCG1 in macrophages 14,15,16,17 .…”
Section: Mainmentioning
confidence: 99%